Were capitalists interested only in profit in the 19th century? An example of Jan Gottlieb Bloch - Pieczewski, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2019)
The social class which was the spiritus movens of rapid economic transformation in the lands of the Kingdom of Poland in the nineteenth century was the bourgeoisie. In the public sphere, there is still a strong conviction among contemporary Poles about the moral defects of capitalists, for whom, according to the prevailing stereotypes, only profit was important. The author of this article, to contradict this claim, gives an example of the life and actions of Jan Gottlieb Bloch (1836–1902). The aim of the article is to present the broad economic, social and scientific activity of Bloch as a member of the bourgeoisie of the Kingdom of Poland. The author also points to the need for further research on the work of Jan Bloch, especially in the field of his economic and irenological writing.